2022
DOI: 10.1039/d1ma01010g
|View full text |Cite
|
Sign up to set email alerts
|

Boron-based non-fullerene small molecule acceptors via nitrogen substitution: a theoretical study

Abstract: The acceptors play vital roles in absorbing sunlight and consequently producing charge in organic solar cells (OSCs). Boron-based non-fullerene acceptors have received particular attention due to their tunable electronic structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Sometimes, the FE state and CT state are mixed together, showing an HCT state. 67,68 As shown in Figure 6, the BTR-Cl/Y6 and BTR-F/Y6 systems have the same proportion of total CT states, which are 40%. However, in BTR-γ-Cl/Y6 and BTR-γ-F/Y6 systems, the proportion of the total CT states are increased to 50 and 45% respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Sometimes, the FE state and CT state are mixed together, showing an HCT state. 67,68 As shown in Figure 6, the BTR-Cl/Y6 and BTR-F/Y6 systems have the same proportion of total CT states, which are 40%. However, in BTR-γ-Cl/Y6 and BTR-γ-F/Y6 systems, the proportion of the total CT states are increased to 50 and 45% respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Getting more CT states is crucial to the generation of photocurrent. Sometimes, the FE state and CT state are mixed together, showing an HCT state. , …”
Section: Resultsmentioning
confidence: 99%
“…They observed that polymer PCPDT functionalized with B-N system showed an improved V OC and PCE, lower HOMO/LUMO levels with a narrower optical bandgap as compared to bare PCPDT polymer. 27 Despite these merits of B-containing p-cores, the development of novel NFAs exhibiting wider absorption in the near-infrared region, 28 and n-type charge transport 25 is a key challenge for further improvement of PCEs in organic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…24 More recently, employing a theoretical approach, Yang et al investigated boron–nitrogen-based A–D–A-type non-fullerene small molecules and demonstrated that the designed acceptors exhibit a wide absorption spectrum with enhanced electron mobility than the bare molecule. 25 Dong et al synthesized the B–N embedded donor–acceptor (D–A) type conjugated polymer. They observed a downshift of the energy levels compared to the bare system.…”
Section: Introductionmentioning
confidence: 99%